Effects of indoor cooking with liquefied petroleum gas versus solid biomass on mosquito and fly density in households - Ian Hennessee; Miles A. Kirby; Xavier Misago; Jackie Mupfasoni; Jiantong Wang; Jean de Dieu Ntivuguruzwa; Florien Ndagijimana; Ghislaine Rosa; Jennifer L. Peel; Lance A. Waller; Joshua P. Rosenthal; Uriel Kitron; et al. (Scientific Reports)
Abstract Cleaner cooking fuels are increasingly promoted to reduce household air pollution-related health effects, but evidence is limited whether changes in cooking fuels could alter vector behavior and human exposure to vector-borne diseases. In the context of a randomized controlled trial in eastern Rwanda, we evaluated differences in mosquito and fly density in 109 intervention houses which received liquefied petroleum gas (LPG) stoves, a continuous fuel supply, and were encouraged to cook indoors compared to 102 control households which continued cooking with biomass fuels, primarily outdoors. Anopheles mosquito densities were similar in the intervention group compared to the control group (RR = 0.92, 95%CI: 0.33–2.55), as were culicine densities (RR = 1.17, 95%CI: 0.83–1.63). In contrast, synanthropic fly densities were 69% lower in intervention households (RR = 0.31, 95% CI: 0.22–0.45). In an exploratory analysis of houses that cooked indoors, Anopheles densities were higher but not significantly different in intervention houses compared to control houses, whereas culicine and synanthropic fly densities were similar. In settings where outdoor cooking with biomass fuels is common, switching to indoor cooking with cleaner-burning fuels does not significantly increase indoor exposure to Anopheles or culicine mosquitoes, while it could significantly reduce exposure to synanthropic flies in kitchen areas.